Therapeutic progress and symptom elevation in treating dismissive attachment: A case study. Issue 1 (2nd January 2019) - Reynolds, Natasha L.; Rupert, David; Sandage, Steven J.
Abstract : A dismissive or avoidant attachment style can present clinical challenges in psychotherapy as the attachment style may interfere with the development of a constructive therapeutic alliance and impact the level of disclosure, expressions of distress, and risks for premature drop-out. This paper reports a naturalistic case study and offers an in-depth examination of a treatment with a client with dismissive attachment, including a detailed examination of relational interventions and countertransference struggles. Furthermore, this paper considers the notable differences between quantitative scores on a well-validated, practice-based clinical symptom inventory and the qualitative outcomes for this client to offer clinical and research implications in treatment with dismissive attachment.